Atuação do engenheiro agrônomo na consultoria agroambiental - Sousa, Thiago Pereira de (Universidade Federal Rural do Semi-Árido, 2018)
The environmental subject was discussed thoroughly, where the concern with the Environment started to win space in the politics of all of the Nations, the environmental conservation started to win larger attention of the society, media and of the Public Power, what culminated in the beginning of Legislative and institutional changes about the activities developed by the man regarding the atmosphere. The demand for services of agronomic and environmental consultancy is increasing due to valorization and recognition of the importance of the environment inside of the productive sections, where the search for adaptation and environmental attendance in the productive processes, where the professionals' of Agrarian Sciences performance was always and it is intimately related with the development of the society, especially in the aspects more directly linked with the farming and the agroindustrialização. Today, the environmental consultancy is a form of I aid those that look for maintain appropriate measures to the execution of the environmental regulation of their enterprises, which consists of an advice gone back to environmental subjects, offered to deprived companies and public, city halls, builders and rural properties, in order to propose services as, for instance, forestation of streets, squares and parks, environmental licensing of activities potentially pollutant, elaboration of plans for recovery of degraded areas and, solution of problems fitossanitários, project of administration of solid residues, environmental diagnosis, among other environmental technical studies.
Monografia
Keywords: Meio Ambiente; Assessoramento; Licenciamento Ambiental; Ciências Agrárias; Environment; Advice; Environmental licensing; Agrarian sciences; CIENCIAS AGRARIAS::AGRONOMIA